1997
DOI: 10.1038/39631
|View full text |Cite
|
Sign up to set email alerts
|

Imprinted expression of the Igf2r gene depends on an intronic CpG island

Abstract: Gametic imprinting is a developmental process that induces parental-specific expression or repression of autosomal and X-chromosome-linked genes. The mouse Igf2r gene (encoding the receptor for insulin- like growth factor type-2) is imprinted and is expressed from the maternal allele after embryonic implantation. We previously proposed that methylation of region 2, a region rich in cytosine-guanine doublets (a 'CpG island') in the second intron of Igf2r, is the imprinting signal that maintains expression of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
373
2
5

Year Published

1998
1998
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 546 publications
(389 citation statements)
references
References 26 publications
9
373
2
5
Order By: Relevance
“…The literature also indicates that mutations were not found in exons 4, 6, and 7 but that polymorphisms were found in exons 4 and 7 [26]. We did not find any p73 mutations in the areas analogous to mutational hot spots in p53, but we cannot exclude that p73 mutations may occur outside these exons or in specific intron regions important in gene regulation [27,28]. Moreover, point mutations in p73 may not be the only way to abrogate or compromise p73 function.…”
Section: Mutation Of the P73 Genecontrasting
confidence: 52%
“…The literature also indicates that mutations were not found in exons 4, 6, and 7 but that polymorphisms were found in exons 4 and 7 [26]. We did not find any p73 mutations in the areas analogous to mutational hot spots in p53, but we cannot exclude that p73 mutations may occur outside these exons or in specific intron regions important in gene regulation [27,28]. Moreover, point mutations in p73 may not be the only way to abrogate or compromise p73 function.…”
Section: Mutation Of the P73 Genecontrasting
confidence: 52%
“…Second, antisense mRNAs were suggested to promote the methylation of sense mRNA promoters. And third, the formation of double-stranded RNA hybrids may interfere with further mRNA processing (Wutz et al, 1997;Lai, 2002;Prescott and Proudfoot, 2002;Tufarelli et al, 2003;Lavorgna et al, 2004;Crampton et al, 2006). These models are not mutually exclusive, and more than one of them may apply to the situation of p53 and WRAP53.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies showed a correlation between methylation status of a CpG rich promoter and the neighboring CpG islands in certain imprinted genes (Ainscough et al, 1997;Wutz et al, 1997). We next determined whether methylation of the VHL CpG island correlated with methylation (demethylation) of its neighboring CpG clusters.…”
Section: Methylation Patterns Of Sequences¯anking the Vhl Genementioning
confidence: 97%